Financial sector development in the Pacific Rim - Itō, Takatoshi, 1950-; Rose, Andrew, 1959- (University of Chicago Press, 2009)
Examines the institutional factors influencing financial innovation, the consequences of financial development, widespread consolidation occurring through mergers and acquisitions, and the implementation of policy reform.--From publisher description.
Papers presented at the 18th Annual East Asia Seminar in Economics, held at Singapore Management University on June 22-24, 2007.
Keywords: Financial institutions -- Pacific Area -- Congresses.; Financial institutions -- East Asia -- Congresses.; Financial crises -- East Asia -- Congresses.; Financial crises -- Pacific Area -- Congresses.; Institutions financières -- Pacifique, Région du -- Congrès.; BUSINESS & ECONOMICS -- Finance.; Financial crises; Financial institutions; East Asia; Pacific Area; Electronic books.; Conference papers and proceedings